2012
DOI: 10.1002/hep.25660
|View full text |Cite
|
Sign up to set email alerts
|

Specific immunization strategies against oxidized low-density lipoprotein: A novel way to reduce nonalcoholic steatohepatitis in mice

Abstract: Background Non-alcoholic steatohepatitis (NASH) is characterized by hepatic lipid accumulation combined with inflammation, which can ultimately progress into cirrhosis. Recently, we demonstrated that deletion of scavenger receptors (SR) CD36 and SR-A in haematopoietic cells reduced hepatic inflammation. In addition to uptake of modified lipoproteins, CD36 and SR-A are also involved in other functions that can activate the inflammatory response. Therefore, the actual trigger for SR activation during NASH is unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(97 citation statements)
references
References 38 publications
5
88
2
2
Order By: Relevance
“…As such, clinicians are cautious with prescribing statins to NASH patients, also because of potential liver damage, particularly in the case of elevated liver enzymes [30]. Experimental evidence further demonstrated that therapy aimed at blocking uptake of oxLDL was successful in preventing the development of NASH in livers of mice [31]. Similar observations were found for a therapy aimed at reducing lysosomal cholesterol in hyperlipidemic mice [32].…”
Section: Underlying Cellular Mechanisms To Cholesterol-induced Hepatisupporting
confidence: 64%
“…As such, clinicians are cautious with prescribing statins to NASH patients, also because of potential liver damage, particularly in the case of elevated liver enzymes [30]. Experimental evidence further demonstrated that therapy aimed at blocking uptake of oxLDL was successful in preventing the development of NASH in livers of mice [31]. Similar observations were found for a therapy aimed at reducing lysosomal cholesterol in hyperlipidemic mice [32].…”
Section: Underlying Cellular Mechanisms To Cholesterol-induced Hepatisupporting
confidence: 64%
“…Serum levels of oxidized metabolites of the n-6 fatty arachidonic and linoleic acids were increased in mice fed a soybean oil-rich high-fat diet compared with mice fed a fish oil-rich high-fat diet (37). Furthermore, oxidized LDL caused Kupffer cell activation in a transgenic mouse model and thus might trigger hepatic inflammation (43). Alternatively, hepatocytes, which are damaged by oxidative stress, may activate Kupffer cells in their vicinity.…”
Section: Main Findingsmentioning
confidence: 97%
“…These macrophage-derived foam cells predominantly contain enlarged lysosomes filled with cholesterol and cholesterol crystals. Additional evidence showed that increased cholesterol storage inside lysosomes of KCs is associated with hepatic inflammation in the context of NASH [71, 72]. …”
Section: Inflammatory Mediators and Immune Alterationsmentioning
confidence: 99%